The Effect of FoMO and Social Media Addiction on Phubbing Behavior in Adolescent K-Pop Fans - Putri, Catherine Agnesia; Sa’id, Mochammad (Utan Kayu Publishing, 2024)
Phubbing, the act of ignoring others in social settings by focusing on one’s smartphone, has become a prevalent issue among adolescent K-Pop fans. This behavior is closely linked to social media addiction and Fear of Missing Out (FoMO), as these fans often seek constant updates about their idols and social networks. The excessive use of social media to satisfy their curiosity and avoid missing out on information can lead to a significant increase in phubbing behavior. This study aims to investigate the effect of FoMO and social media addiction on phubbing behavior among adolescent K-Pop fans. Using a quantitative correlational approach, 193 adolescents aged 10-21 years were surveyed. The study employed the Generic Scale of Phubbing (GSP), Online Fear of Missing Out Scale (ON-FoMO), and the Bergen Social Media Addiction Scale (BSMAS) to assess phubbing behavior, FoMO, and social media addiction, respectively. The results indicate that the majority of participants have low levels of FoMO (48.7%) but high levels of social media addiction (46.1%), with 53.4% exhibiting low phubbing behavior. Multiple linear regression analysis shows a significant positive effect of both FoMO and social media addiction on phubbing behavior, with FoMO contributing 36% and social media addiction contributing 22.9% to the variance in phubbing behavior. Together, these variables explain 58.9% of phubbing behavior among the participants. The study supports the Usability and Satisfaction Theory, emphasizing the role of FoMO and social media addiction in promoting excessive smartphone use during social interactions. Practical implications include the need for interventions to manage adolescents' social media usage and mitigate the psychological effects of FoMO to enhance healthy social engagement. Future research should explore longitudinal relationships and consider socio-environmental factors to better understand the causes of phubbing behavior in adolescents.